Paradigm Shift in Treatment of Alzheimer's Disease: Zinc Therapy Now a Conscientious Choice for Care of Individual Patients. (22nd September 2011) - Hoogenraad, Tjaard U.
Abstract : Breakthrough in treatment of Alzheimer's disease with a shift from irrational dangerous chelation therapy to rational safe evidence based oral zinc therapy. Evidence based medicine: After synthesizing the best available clinical evidence I conclude that oral zinc therapy is a conscientious choice for treatment of free copper toxicosis in individual patients with Alzheimer's disease. Hypothesis 1: Age related free copper toxicosis is a causal factor in pathogenesis of Alzheimer's disease. There are 2 neurodegenerative diseases with abnormalities in copper metabolism: (a) the juvenile form with degeneration in the basal ganglia (Wilson's disease) and (b) the age related form with cortical neurodegeneration (Alzheimer's disease). Initially the hypothesis has been that neurodegeneration was caused by accumulation of copper in the brain but later experiences with treatment of Wilson's disease led to the conviction that free plasma copper is the toxic form of copper: it catalyzes amyloid formation thereby generating oxidative stress, free radicals and degeneration of cortical neurons. Hypothesis 2: Oral zinc therapy is an effective and safe treatment of free copper toxicosis in Alzheimer's disease. Proposed dosage: 50 mg elementary zinc/day. Warning: Chelation therapy is irrational and dangerous in treatment of copper toxicosis in Alzheimer's disease.